Interrupting antiretroviral treatment in HIV cure research: scientific and ethical considerations - Samual A. Garner; Stuart Rennie; Jintanat Ananworanich; Karine Dube; David M. Margolis; Jeremy Sugarman; Randall Tressler; Adam Gilbertson; Liza Dawson (Elsevier, 2017)
Over the past several years there has been intense activity directed at the possibility of achieving remission or eradication of HIV infection. Current assays for the measurement of latent HIV are insufficient to demonstrate complete clearance of replication-competent HIV. Therefore, the ultimate test for assessing whether investigational interventions have resulted in HIV remission or eradication is to interrupt standard antiretroviral therapy (ART) in a carefully controlled clinical trial setting. These procedures, known as analytic treatment interruptions (ATIs), raise important scientific and ethical questions. The lack of definitive assays for measuring viral reservoirs not only makes research on HIV remission or cure challenging, it also affects the ability to assess risks from ATIs themselves. In spite of these challenges, basic ethical criteria can be met with careful study design and close monitoring. In this brief report we outline ethical standards for HIV cure research involving ATIs. These criteria should be revisited as the science evolves.